From development to yield: genetic and molecular regulation of agronomic traits in maize seeds - Ajayo, Babatope Samuel; Huang, Yubi; Hu, Yufeng (Frontiers in Plant Science, 2026)
Maize (Zea mays L.) plays a critical role in global food security. The challenge of climate pressures and rising population demands emphasizes the urgent need for high-yield, nutrient-rich and resilient cultivars. This review synthesizes the genetic and molecular mechanisms driving maize seed formation, highlighting the development of the embryo, endosperm, and seed coat that influence agronomic traits like kernel size, weight, vigor, and nutritional quality. We investigate how early events, from double fertilization through embryogenesis, endosperm development, and seed coat formation, set the stage for final seed traits. Recent studies, including genome-wide association studies, comparative genomics, candidate-gene analysis, and multi-omics approaches, have shed light on the complex genetic architecture underpinning these seed traits. These studies have identified key regulatory networks involving transcription factors and phytohormonal signals essential for seed development in maize. We also highlight the important molecular pathways that govern starch and protein biosynthesis, alongside nutrient transport processes that are crucial for seed filling. Despite significant advancements, challenges remain in functional validations and integrating multi-omics data across various contexts. Looking ahead, harnessing these insights can drive the breeding of maize cultivars that are resilient, nutrient-dense, and capable of meeting the challenges posed by climate change and rising food demand, ultimately supporting global food security.